ANALYZING INDONESIAN CURRICULUM OF KTSP - Chaira, Salwa (Getsempena English Education Journal, 2015)
This article is to explain the implementation of KTSP curriculum which is invented in 2006 and is still implemented in some schools in Indonesia. Here, the writer includes several aspects, which are the current status of the curriculum, the relationship of curriculum with the mainstream environment, the organizing principle of the curriculum, theoretical approach of the curriculum, the theory of language learning, the curriculum and its context, curriculum and syllabus assessment. The method applied here is a library analysis toward KTSP curriculum. The result shows that the curriculum suits Indonesian students in almost sides since it requires teachers to develop the curriculum based on the context of schools and studentsâ capacity. Besides, the students will not face huge burden learning in a school since the teachers who formally recognize their students well develop all the teaching and learning syllabi. In conclusion, KTSP is a practically appropriate curriculum which has been implemented compared to previous curriculums. Indonesian government design it since this is a better innovative curriculum to apply to the educational institutions in Indonesia. The demand of the curriculum appears neither low nor high and is definitely achieved by the students.Â Â Key Words: Analyzing, Curriculum, KTSP